The ROLE OF RELIGIOSITY IN ENCOURAGING SUSTAINABLE MANAGEMENT PRACTICES TO IMPROVE MSME BUSINESS PERFORMANCE - Kemala, Sri; Wahab, Nadratun Nafisah Abdul (PENANOMICS: International Journal of Economics, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the economy, yet face challenges in maintaining economic, social, and environmental sustainability amidst increasingly fierce business competition. The importance of this research lies in understanding the internal factors that can strengthen sustainable management practices, one of which is religiosity. This study aims to analyze the role of religiosity in encouraging sustainable management practices to improve MSME business performance. This research uses a literature review approach, with data sources obtained from reputable academic databases such as Scopus, ScienceDirect, JSTOR, Emerald Insight, and Google Scholar. The results of the study indicate that religiosity, both intrinsic and extrinsic, plays a significant role in shaping managers' ethical behavior, strengthening a sustainable organizational culture, and improving governance, innovation, and stakeholder relations. This has a positive impact on overall business resilience and performance. In conclusion, religiosity serves as a moral and strategic foundation capable of addressing sustainability challenges through the integration of ethical values ​​into managerial practices. This research contributes to the development of the concept of religious-based sustainable management and opens up further research directions to test empirical models of the relationship between religiosity and sustainable performance in various MSME sectors.